Distinguishing isomeric aldohexose‐ketohexose disaccharides by electrospray ionization mass spectrometry in positive mode. (30th November 2015) - Yuan, Hang; Liu, Liu; Gu, Jinping; Liu, Yan; Fang, Meijuan; Zhao, Yufen
<x xml:space="preserve">Abstract</x> Rationale The identification of the structure of carbohydrates is challenging because of their complex composition of monosaccharide units, linkage position and anomeric configuration. We used a combination of principle component analysis (PCA) and tandem mass spectrometry (MS/MS), including collision‐induced dissociation (CID) and higher energy collision dissociation (HCD), to distinguish four aldohexose‐ketohexose isomers, sucrose, turanose, maltulose, and palatinose, which are composed of glucose and fructose. Methods The electrospray ionization (ESI)‐MS/MS spectra of the lithium and sodium adducts of the glucopyranosyl fructose (Glc‐Fru) isomers were recorded on two independent mass spectrometers using CID (MicroTOF QII) and HCD (Q‐Exactive Orbitrap). The differences between the fragment ions were evaluated by the PCA models. The glycosidic bond cleavage mechanism of lithiated sucrose was verified by a deuterium‐labeling experiment combined with density functional theory calculations (Gaussian 09). Results The main fragment ions in the MS/MS spectra from the glycosidic bond decomposition, cross‐ring cleavage (−90 Da), and dehydration of the precursor ions of m/z 349 ([M+Li]+) and m/z 365 ([M+Na]+) were observed. Surprisingly, cross‐ring cleavage and dehydration of the precursor ions were rarely observed in both lithiated and sodiated sucrose. There were significant differences in the fragmentation patterns and relative abundances of fragment ions in second‐order mass spectrometry, which allowed discriminant models to be constructed for the alkali adducts and collision modes. Conclusions Glc‐Fru isomers were discriminated in the PCA score plots for their lithium and sodium adducts by using different collision modes. The results showed that HCD‐MS/MS is an ideal tool for differentiating lithium adducts, whereas, CID‐MS/MS is better for discriminating sodium adducts. The hydrogen migration of the hydroxyl group at C3 of the fructose unit caused the glycosidic bond decomposition of lithiated sucrose. Copyright © 2015 John Wiley & Sons, Ltd.